2020
DOI: 10.4236/ajps.2020.116067
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of the Moroccan Endemic Plant <i>Thymus broussonetii</i> Boiss. with Aromatic-Medicinal Value and Conservation Concern

Abstract: Micropropagation from shoot tips and nodal segments was carried out for the conservation and domestication of spontaneous Moroccan thyme, Thymus broussonetii Boiss. subsp. broussonetii (endemic threatened). The mineral composition of the culture medium, as well as the succession of different growth regulators, influenced the in vitro growth of this species. Sterilized achenes of T. broussonetii were able to germinate on an agar medium containing Gautheret macronutrients with a rate of 25% and a degree of conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The study of the effect of polyamines alone or in combination with cytokinins or/and auxins has been addressed in investigations of other species belonging to the Lamiaceae family. El Ansari et al (2020) [35] showed that medium supplemented with 10 µM Spermine gave the best results in terms of bud, shoot and root multiplication, and Sarropoulou and Maloupa (2019) [36] showed that the integration of exogenous polyamines contributed to numerous modifications in the growth of Sideritis raeseri Boiss. & Heldr.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the effect of polyamines alone or in combination with cytokinins or/and auxins has been addressed in investigations of other species belonging to the Lamiaceae family. El Ansari et al (2020) [35] showed that medium supplemented with 10 µM Spermine gave the best results in terms of bud, shoot and root multiplication, and Sarropoulou and Maloupa (2019) [36] showed that the integration of exogenous polyamines contributed to numerous modifications in the growth of Sideritis raeseri Boiss. & Heldr.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kizil and Khawar (2017) [35] reported that the proliferation and regeneration of Origanum acutidens shoots was maximal in medium supplemented with 0.8 µM BAP. Moreover, the type and concentration of cytokinins were evaluated in other species of the Lamiaceae family ( [36] [37] [38] [39]).…”
Section: Discussionmentioning
confidence: 99%
“…Application of polyamines alone, including spermine and spermidine at concentrations greater than 10 µM, inhibits the root formation of Lavandula × intermedia "Grosso" vitroplants (Erland and Mahmoud 2014) [51]. El Ansari et al (2019) [36] found that the best propagation of buds, shoots and roots of Thymus vulgaris L. was marked in the medium supplemented with 10 µM spermine and demonstrated that 50 µM spermidine was effective for better propagation of roots whereas 10 µM of the same polyamine was favorable for root propagation.…”
Section: Discussionmentioning
confidence: 99%